Systemic risk in the Finnish payment system: An empirical investigation - Harri Kuussaari (Bank of Finland, 1996)
The volume of large-value funds transfers in the money, foreign exchange and securities markets has increased manifold during the last decade.This development has increased interbank debt positions and extensions of intraday credit resulting from payment transactions in the payment-intermediation sector. Systemic risk in these arrangements refers to the risk that one clearing system participant's failure to settle will cause one or more other participants to default.The danger of systemic failure exists in a clearing system in which payment messages are exchanged during the day but funds are transferred only at the end of the day.In this study, simulation with empirical data is used to measure the probability, extent and resulting effects of a systemic crisis in the Finnish payment system. The major finding of the study is that one participant's failure to settle in the Finnish payment system can cause serious problems for other participants but the danger of systemic failure is relatively small.On average the banks' largest counterparty risks are low and amount to less than 10 per cent of their own funds.However, on some days counterparty risk can amount to over 50 per cent of banks' own funds and thus constitute a systemic risk.Large counterparty risks however do not form long interbank chains that could lead to a domino effect.Even should a payment system participant suddenly be unable to settle, the other participants would probably manage to avoid serious problems. Although the simulation results indicate that presently the probability of systemic crisis in Finland is quite small, it is still important that payment system risk control be further developed.The environment in which the payment system operates is developing very rapidly, and risks are growing as volumes increase.As the system opens up to foreign credit institutions, Finnish payment system participants also find themselves dealing with more and more counterparties about whom they have no prior knowledge.System entry and risk control can no longer be based solely on trust; clear game rules are needed.As part of its task of overseeing payment systems, the central bank will need to closely monitor system developments, promote risk awareness in the markets and payment systems, and prevent the creation of systems in which it is possible for settlement failures to spread.This work should be done in cooperation with international organizations and the EU.
URN:NBN:fi:bof-20140807626
Keywords: 330; systemic risk; clearing; settlement; Finland